78.8k views
2 votes
Question: Write the equation of a parabola having the vertex (1, −2) and containing the point (3, 6) in vertex form. Then, rewrite the equation in standard form.

[Hint: Vertex form: y - k = a(x - h)2]

User SRR
by
6.3k points

1 Answer

4 votes

Answer:


y+2=2(x-1)^(2) -----> vertex form


y=2x^(2)-4x -----> standard form

Explanation:

we know that

The equation of a vertical parabola in vertex form is equal to


y-k=a(x-h)^(2)

where

(h,k) is the vertex of the parabola

In this problem we have


(h,k)=(1,-2)


Point(3,6)

substitute the values and solve for a


6-(-2)=a(3-1)^(2)


8=a(2)^(2)


8=a(4)


a=2

the equation in vertex form is equal to


y+2=2(x-1)^(2)

Find the equation of the parabola in standard form

we know that

the equation of the parabola in standard form is equal to


y=ax^(2)+bx+c

we have


y+2=2(x-1)^(2)

convert to standard form


y+2=2(x^(2)-2x+1)\\ \\y+2= 2x^(2)-4x+2\\ \\y=2x^(2)-4x+2-2\\ \\y=2x^(2)-4x

User Anton Tarasenko
by
6.4k points